Acceptability Test and Nutritional Analysis of Tempeh and Moringa Leaf Soft Rice as Complementary Foods (MP-ASI) - Nadira Citra Pertiwi; Kurnia Mar’atus Solichah; Diah Puspitasari (PT Inovasi Pratama Internasional, 2026)
The age of 6–24 months is a crucial period for a child's growth and development, requiring optimal nutritional intake through the provision of Complementary Foods (MP-ASI). MP-ASI serves to supplement nutritional needs that can no longer be met by breast milk alone. Tempeh, as a source of plant-based protein, and moringa leaves, which are rich in iron and vitamins, have the potential to be developed into